The Changes in Color of Pineapple Stem Extract (Ananas comosus (L.) Merr) with Carbamide Peroxide as a Dental Bleach toward Dental Surface Violence in Vitro - Deli Mona; Laura Ajeng Dyalova (Majalah Kedokteran Andalas)
Objective: The purpose of this research was to determine the effectiveness comparison of pineapple stem extract (Ananas comosus (L.) Merr) and carbamide peroxide home bleaching for tooth whitening agent.